Chronic Co-Administration of Sepiapterin and L-Citrulline Ameliorates Diabetic Cardiomyopathy and Myocardial Ischemia/Reperfusion Injury in Obese Type 2 Diabetic Mice. (January 2016) - Baumgardt, Shelley L.; Paterson, Mark; Leucker, Thorsten M.; Fang, Juan; Zhang, David X.; Bosnjak, Zeljko J.; Warltier, David C.; Kersten, Judy R.; Ge, Zhi-Dong
Abstract : Background—: Diabetic heart disease is associated with tetrahydrobiopterin oxidation and high arginase activity, leading to endothelial nitric oxide synthase dysfunction. Sepiapterin (SEP) is a tetrahydrobiopterin precursor, and L-citrulline (L-Cit) is converted to endothelial nitric oxide synthase substrate, L-arginine. Whether SEP and L-Cit are effective at reducing diabetic heart disease is not known. The present study examined the effects of SEP and L-Cit on diabetic cardiomyopathy and ischemia/reperfusion injury in obese type 2 diabetic mice. Methods and Results—: Db/db and C57BLKS/J mice at 6 to 8 weeks of age received vehicle, SEP, or L-Cit orally alone or in combination for 8 weeks. Cardiac function was evaluated with echocardiography. Db/db mice displayed hyperglycemia, obesity, and normal blood pressure and cardiac function compared with C57BLKS/J mice at 6 to 8 weeks of age. After vehicle treatment for 8 weeks, db/db mice had reduced ejection fraction, mitral E / A ratio, endothelium-dependent relaxation of coronary arteries, tetrahydrobiopterin concentrations, ratio of endothelial nitric oxide synthase dimers/monomers, and nitric oxide levels compared with vehicle-treated C57BLKS/J mice. These detrimental effects of diabetes mellitus were abrogated by co-administration of SEP and L-Cit. Myocardial infarct size was increased, and coronary flow rate and ±d P /d t were decreased during reperfusion in vehicle-treated db/db mice subjected to ischemia/reperfusion injury compared with control mice. Co-administration of SEP and L-Cit decreased infarct size and improved coronary flow rate and cardiac function in both C57BLKS/J and db/db mice. Conclusions—: Co-administration of SEP and L-Cit limits diabetic cardiomyopathy and ischemia/reperfusion injury in db/db mice through a tetrahydrobiopterin/endothelial nitric oxide synthase/nitric oxide pathway. Abstract : Supplemental Digital Content is available in the text.